Pajelanças e Cultos Pretos em Manaus (1904 a 1940) - Tenório, Adriano Magalhães (2021)
This is a historical survey on the presence of Afro-Brazilian religions and shamanism in the city of Manaus (AM), from 1904 to 1940. According to research, in Brazil the period is characterized by criminalization and persecution of cults and / or popular magical religious practices, promoted by the State, through the police and justice. Allied to the State, the written press was a strong arm in this process, especially when it started to investigate and inform against the “exploiters of public credulity”, “healers”, “sorcerers” and suchlike in its content, urging competent authorities to act on the issues. In addition to the exposure, it also widely publicized police actions, which arrested practitioners and shut spaces of worship, it was also typical the creation of campaigns that went on through long texts publications against those practices. Journalistic sources have been used in researches on this topic for some time and the results have shown thought-provoking matters. For this research, the historical sources will also be the journalistic ones, news present in the Jornal do Comércio do Amazonas, which carry in its publications the same matters that brought up the previous researches. Through them, in addition to observing the criminalization process, we noticed, in the journalistic discourse, particularities of the cults and practices held in Manaus. It is through the analysis of these elements and their differences that this research was built and we can certify the presence of black and local cults.